Evaluation Policy and Integral Education Program in the High School of Pernambuco State Education System: the limits of the centrality of evaluation in education policy (Práxis Educativa, 2017)
This paper aimed at evaluating the results of the relationship between 1. The Educational Responsibility Policy; 2. The Evaluation Policy defined by the Pernambuco State Education System; and 3. The process of implementation of the Integral Education Program (PEI, Brazilian Portuguese abbreviation) in High School Reference Institutions (EREMs, Brazilian Portuguese abbreviation) and in the State Technical Schools (ETEs, Brazilian Portuguese abbreviation). Based on document and content analyses, a qualitative study was carried out whose data collection instruments were interviews with managers, teachers, students and technicians, along with questionnaires applied to the students. The theoretical background included Freitas (2012), Ravitch (2011), Algebaile (2009), among others. The results revealed that in the PEI implementation process, the evaluation through results is related to command-and-control strategies which broaden and intensify teachers’ and students’ school hours, working as a neoliberal and managerial laboratory in education. From this research perspective, the conclusion was that strategies such as increasing the years of study and the school hours disguise problems such as the crisis of structural unemployment and the reduction in investments provided for in social policies as a whole. Keywords: Evaluation. Curriculum. Integral Education.